UJI KINERJA MESIN PENGOLAH GULA SEMUT HORJA MPN20 DI KELOMPOK TANI KARYA TANI DESA TALAITAD KECAMATAN SULUUN TARERAN KABUPATEN MINAHASA SELATAN - Stenli F. E. Pomantow; Lady C. Ch. E. Lengkey; Robert Molenaar (COCOS, 2021)
Abstract The purpose of this study is to evaluate the performance of palm sugar processing machine HORJA MPN20 including temperature conditions, product yield, energy consumption and energy efficiency of palm sugar processing machine HORJA MPN20 located in the farmer group Karya Tani. The results showed that the average fire temperature in the first to third experiments was 205.30ËšC, 214.4ËšC, and 240.4ËšC, respectively. The yields in the first to third experiments were respectively 9.47%, 10.40%, 11.03% with an average of 10.30%. Gas energy consumption in the first to third experiments were 136,533,62 kJ, 136,533,62 kJ, 141,241.68 kJ with an average of 138,102,98 kJ. The consumption of electrical energy in the first to third experiments were 711.48 kJ, 323.40 kJ, 662.97 kJ with an average of 565.95 kJ. Human energy consumption in the first to third experiments were 502.08 kJ, 313.8 kJ, 376.56 kJ with an average of 397.48 kJ. The energy efficiency of the engine in the first to third experiments was respectively 44.56%, 44.29%, 42.39% with an average of 43.75%. Key words: palm sugar, processing machine , performance, efficiency